Skip to content
GitLab
Explore
Sign in
Primary navigation
Search or go to…
Project
U
uva
Manage
Activity
Members
Labels
Plan
Issues
Issue boards
Milestones
Wiki
Code
Merge requests
Repository
Branches
Commits
Tags
Repository graph
Compare revisions
Build
Pipelines
Jobs
Pipeline schedules
Artifacts
Deploy
Releases
Model registry
Operate
Environments
Monitor
Incidents
Analyze
Value stream analytics
Contributor analytics
CI/CD analytics
Repository analytics
Model experiments
Help
Help
Support
GitLab documentation
Compare GitLab plans
Community forum
Contribute to GitLab
Provide feedback
Keyboard shortcuts
?
Snippets
Groups
Projects
Show more breadcrumbs
Taddeüs Kroes
uva
Commits
0b3c4094
Commit
0b3c4094
authored
13 years ago
by
Sander Mathijs van Veen
Browse files
Options
Downloads
Plain Diff
Merge branch 'master' of vo20.nl:/git/uva
parents
6c6d35c3
e37f59f9
No related branches found
Branches containing commit
No related tags found
No related merge requests found
Changes
3
Hide whitespace changes
Inline
Side-by-side
Showing
3 changed files
.gitignore
+1
-0
1 addition, 0 deletions
.gitignore
funclang-taddeus/series2/ass5.ml
+85
-0
85 additions, 0 deletions
funclang-taddeus/series2/ass5.ml
funclang-taddeus/series2/series2.tex
+161
-0
161 additions, 0 deletions
funclang-taddeus/series2/series2.tex
with
247 additions
and
0 deletions
.gitignore
+
1
−
0
View file @
0b3c4094
...
...
@@ -16,5 +16,6 @@ robotica/
*.toc
*.cmi
*.cmo
*.exe
*#
*~
This diff is collapsed.
Click to expand it.
funclang-taddeus/series2/ass5.ml
+
85
−
0
View file @
0b3c4094
...
...
@@ -2,3 +2,88 @@
let
isLeapYear
y
=
y
>
1582
&&
y
mod
4
=
0
&&
(
y
mod
100
!=
0
||
y
mod
400
=
0
)
;;
(* Test the isLeapYear function with a number of known leap years *)
let
test_isLeapYear
y
expect
=
let
yields
=
isLeapYear
y
in
Printf
.
printf
"%d -> %s, (should be %b, yields %b)
\n
"
y
(
if
yields
=
expect
then
"success"
else
"failure"
)
expect
yields
;;
test_isLeapYear
1500
false
;;
test_isLeapYear
1900
false
;;
test_isLeapYear
1904
true
;;
(* Give a proper English character string representation of a date *)
let
date2str
day
month
year
=
if
day
<
1
||
day
>
31
||
month
<
1
||
month
>
12
||
year
<
0
then
raise
(
Failure
"invalid date"
)
else
(* Get the textual postfix of a day number *)
let
getDayPostfix
day
=
match
day
with
1
|
21
|
31
->
"st"
|
2
|
22
->
"nd"
|
3
|
23
->
"rd"
|
_
->
"th"
in
let
months_str
=
[
"January"
;
"February"
;
"March"
;
"April"
;
"May"
;
"June"
;
"July"
;
"August"
;
"September"
;
"October"
;
"November"
;
"December"
]
in
let
month_str
=
List
.
nth
months_str
(
month
-
1
)
in
Printf
.
sprintf
"%s %d%s, %4d"
month_str
day
(
getDayPostfix
day
)
year
;;
(* Test the date2str function with a few common and exceptional cases *)
let
test_date2str
d
m
y
expect
=
let
str
=
(
date2str
d
m
y
)
in
Printf
.
printf
"%d %d %d -> %s, (should be %s, yields %s)
\n
"
d
m
y
(
if
str
=
expect
then
"success"
else
"failure"
)
expect
str
;;
test_date2str
1
1
2010
"January 1st, 2010"
;;
test_date2str
9
2
2010
"February 9th, 2010"
;;
test_date2str
3
3
2011
"March 3rd, 2011"
;;
test_date2str
22
12
2012
"December 22nd, 2012"
;;
(* Sum all digits of a natural number *)
let
rec
sum_digits
n
=
if
n
<
0
then
raise
(
Failure
"cannot sum digits in integers below 0"
)
else
let
str
=
string_of_int
n
in
let
l
=
String
.
length
str
in
if
l
=
1
then
int_of_string
str
else
int_of_char
str
.
[
0
]
-
48
+
sum_digits
(
int_of_string
(
String
.
sub
str
1
(
l
-
1
)))
;;
(* Get the digital root of a natural number n *)
let
rec
digitRoot
n
=
let
sum
=
sum_digits
n
in
if
(
String
.
length
(
string_of_int
sum
)
=
1
)
then
sum
else
(
digitRoot
sum
)
;;
(* Test the digitRoot function for a few known solutions *)
let
test_digitRoot
n
expect
=
let
root
=
digitRoot
n
in
Printf
.
printf
"%d -> %s, (should be %d, yields %d)
\n
"
n
(
if
root
=
expect
then
"success"
else
"failure"
)
expect
root
;;
test_digitRoot
123
6
;;
test_digitRoot
65536
7
;;
(* Check if a given string is a palindrome *)
let
rec
isPalindrome
str
=
let
l
=
(
String
.
length
str
)
in
l
<
2
||
(
str
.
[
0
]
=
str
.
[
l
-
1
]
&&
(
isPalindrome
(
String
.
sub
str
1
(
l
-
2
))))
;;
(* Test the isPalindrome function with a few known palindromes *)
let
test_isPalindrome
str
expect
=
let
result
=
(
isPalindrome
str
)
in
Printf
.
printf
"%s -> %s, (should be %b, yields %b)
\n
"
str
(
if
result
=
expect
then
"success"
else
"failure"
)
expect
result
;;
test_isPalindrome
"foo"
false
;;
(* non-palindrome of odd length *)
test_isPalindrome
"foobar"
false
;;
(* non-palindrome of even length *)
test_isPalindrome
"lepel"
true
;;
(* palindrome of odd length *)
test_isPalindrome
"foof"
true
;;
(* palindrome of even length *)
test_isPalindrome
""
true
;;
(* The empty string is a palindrome *)
This diff is collapsed.
Click to expand it.
funclang-taddeus/series2/series2.tex
0 → 100644
+
161
−
0
View file @
0b3c4094
\documentclass
[10pt,a4paper]
{
article
}
\usepackage
[english]
{
babel
}
\usepackage
[utf8]
{
inputenc
}
\usepackage
{
amsmath,hyperref,graphicx,booktabs,float,listings
}
% Paragraph indentation
\setlength
{
\parindent
}{
0pt
}
\setlength
{
\parskip
}{
1ex plus 0.5ex minus 0.2ex
}
\title
{
Functional Languages - Assignment series 2
}
\author
{
Tadde
\"
us Kroes (6054129)
}
\begin{document}
\maketitle
\section
{
Assignment 4
}
Assignment:
\emph
{
Define the Boolean functions negation, disjunction and
conjunction as
$
\lambda
$
-terms.
}
\newcommand
{
\s
}{
\hspace
{
2mm
}}
\newcommand
{
\true
}{
\lambda
a.
\lambda
b.a
}
\newcommand
{
\truea
}{
\lambda
u.
\lambda
v.u
}
\newcommand
{
\false
}{
\lambda
a.
\lambda
b.b
}
\newcommand
{
\falsea
}{
\lambda
u.
\lambda
v.v
}
\subsection
{
Negation
}
Negation flips the value of a boolean (TRUE becomes FALSE and vice versa).
Consider
$
\neg
=
\lambda
b.
\lambda
x.
\lambda
y.
((
b
\s
y
)
\s
x
)
$
.
Given that
$
TRUE
=
\true
$
and
$
FALSE
=
\false
$
, we can make the following
derivations:
\begin{table}
[H]
\begin{tabular}
{
rl
}
$
\neg
TRUE
$
&
$
=
(
\lambda
b.
\lambda
x.
\lambda
y.
((
b
\s
y
)
\s
x
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
\lambda
x.
\lambda
y.
((
\true
\s
y
)
\s
x
)
$
\\
&
$
\rightarrow
_{
\beta
}
\lambda
x.
\lambda
y.
(
\lambda
b.y
\s
x
)
$
\\
&
$
\rightarrow
_{
\beta
}
\lambda
x.
\lambda
y.y
$
\\
&
$
\equiv
_{
\alpha
}
FALSE
$
\\
&
\\
$
\neg
FALSE
$
&
$
=
(
\lambda
b.
\lambda
x.
\lambda
y.
((
b
\s
y
)
\s
x
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
\lambda
x.
\lambda
y.
((
\false
\s
y
)
\s
x
)
$
\\
&
$
\rightarrow
_{
\beta
}
\lambda
x.
\lambda
y.
(
\lambda
b.b
\s
x
)
$
\\
&
$
\rightarrow
_{
\beta
}
\lambda
x.
\lambda
y.x
$
\\
&
$
\equiv
_{
\alpha
}
TRUE
$
\\
\end{tabular}
\end{table}
TRUE and FALSE are both flipped, so the function
$
\neg
$
is correct.
\pagebreak
\subsection
{
Disjunction
}
The disjunction function
$
\vee
$
should have the following properties:
\\
TRUE
$
\vee
$
TRUE = TRUE
\\
TRUE
$
\vee
$
FALSE = TRUE
\\
FALSE
$
\vee
$
TRUE = TRUE
\\
FALSE
$
\vee
$
FALSE = FALSE
Consider
$
\vee
=
\lambda
p.
\lambda
q.
((
p
\s
p
)
\s
q
)
$
. Given the functions for
TRUE and FALSE, the combination of the following derivations proves that the
function
$
\vee
$
is correct:
\begin{table}
[H]
\begin{tabular}
{
rl
}
$
TRUE
\s\vee\s
TRUE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
p
)
\s
q
)
\s
\true
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\true
\s
\true
)
\s
q
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\true
\s
\true
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\alpha
,
\beta
}
(
\lambda
b.
\truea
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
\truea
$
\\
&
$
\equiv
_{
\alpha
}
TRUE
$
\\
&
\\
$
TRUE
\s\vee\s
FALSE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
p
)
\s
q
)
\s
\false
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\true
\s
\true
)
\s
q
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\true
\s
\true
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\alpha
,
\beta
}
(
\lambda
b.
\truea
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
\truea
$
\\
&
$
\equiv
_{
\alpha
}
TRUE
$
\\
&
\\
$
FALSE
\s\vee\s
TRUE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
p
)
\s
q
)
\s
\true
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\false
\s
\false
)
\s
q
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\false
\s
\false
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
b.b
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
\true
$
\\
&
$
\equiv
_{
\alpha
}
TRUE
$
\\
&
\\
$
FALSE
\s\vee\s
FALSE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
p
)
\s
q
)
\s
\false
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\false
\s
\false
)
\s
q
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\false
\s
\false
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
b.b
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
\false
$
\\
&
$
\equiv
_{
\alpha
}
FALSE
$
\\
\end{tabular}
\end{table}
\pagebreak
\subsection
{
Conjunction
}
The disjunction function
$
\wedge
$
should have the following properties:
\\
TRUE
$
\wedge
$
TRUE = TRUE
\\
TRUE
$
\wedge
$
FALSE = FALSE
\\
FALSE
$
\wedge
$
TRUE = FALSE
\\
FALSE
$
\wedge
$
FALSE = FALSE
Consider
$
\wedge
=
\lambda
p.
\lambda
q.
((
p
\s
q
)
\s
p
)
$
. Given the functions for
TRUE and FALSE, the combination of the following derivations proves that the
function
$
\wedge
$
is correct:
\begin{table}
[H]
\begin{tabular}
{
rl
}
$
TRUE
\s\wedge\s
TRUE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
q
)
\s
p
)
\s
\true
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\true
\s
q
)
\s
\true
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\true
\s
\true
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\alpha
,
\beta
}
(
\lambda
b.
\truea
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
\truea
$
\\
&
$
\equiv
_{
\alpha
}
TRUE
$
\\
&
\\
$
TRUE
\s\wedge\s
FALSE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
q
)
\s
p
)
\s
\false
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\true
\s
q
)
\s
\true
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\true
\s
\false
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\alpha
,
\beta
}
(
\lambda
b.
\falsea
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
\falsea
$
\\
&
$
\equiv
_{
\alpha
}
FALSE
$
\\
&
\\
$
FALSE
\s\wedge\s
TRUE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
q
)
\s
p
)
\s
\true
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\false
\s
q
)
\s
\false
)
\s
\true
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\false
\s
\true
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
b.b
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
\false
$
\\
&
$
\equiv
_{
\alpha
}
FALSE
$
\\
&
\\
$
FALSE
\s\wedge\s
FALSE
$
&
$
=
(
\lambda
p.
(
\lambda
q.
((
p
\s
q
)
\s
p
)
\s
\false
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
q.
((
\false
\s
q
)
\s
\false
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
((
\false
\s
\false
)
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
(
\lambda
b.b
\s
\false
)
$
\\
&
$
\rightarrow
_{
\beta
}
\false
$
\\
&
$
\equiv
_{
\alpha
}
FALSE
$
\\
\end{tabular}
\end{table}
\section
{
Assignment 5
}
See appendix
\ref
{
appendix:ass5
}
(file
\emph
{
ass5.ml
}
) for my implementation
of the functions
\texttt
{
isLeapYear
}
,
\texttt
{
date2str
}
,
\texttt
{
digitRoot
}
and
\texttt
{
isPalindrome
}
.
\pagebreak
\appendix
\section
{
ass5.ml
}
\label
{
appendix:ass5
}
\lstinputlisting
{
ass5.ml
}
\end{document}
This diff is collapsed.
Click to expand it.
Preview
0%
Loading
Try again
or
attach a new file
.
Cancel
You are about to add
0
people
to the discussion. Proceed with caution.
Finish editing this message first!
Save comment
Cancel
Please
register
or
sign in
to comment